2.8. Some Important Inequalities#

Theorem 2.59

Let 0<λ<1. Then

(2.3)#tλ1λ+λtt0.

The inequality becomes equality only when t=1.

Proof. Define f:RR with domf=R+ by

f(t)1λ+λttλ.

Then,

f(t)=λλtλ1=λ(11t1λ).

In particular, note that f(1)=0 and:

f(t){>0, if t>1<0, if 0<t<1.

Thus, f has a minimum value at t=1 which is f(1)=0. Thus, f(t)0 for all t0.

Thus,

1λ+λttλ0tλ1λ+λtt0.

For t=1,

1λ+λt=1=1λ.

Thus, the inequality indeed reduces to equality at t=1.

Definition 2.89 (Conjugate exponent)

Let p,q be extended real numbers with p,q[1,]. Then, p and q are called conjugate exponents if

1p+1q=1.

In particular 1 and are conjugate exponents in R.

Example 2.14 (Conjugate exponents)

  1. p=1 and q=.

  2. p=2/3 and q=3.

  3. p=2 and q=2.

  4. p=3 and q=2/3.

  5. p= and q=1.

Theorem 2.60 (Characterization of conjugate exponents)

Let p,q be extended real numbers with p,q[1,].

The following are equivalent:

  1. p and q are conjugate exponents.

  2. 1p=q1q.

  3. p=qq1.

  4. 1q=p1p.

  5. q=pp1.

Proof. We get these results by simple arithmetic.

1p+1q=11p=11q1p=q1qp=qq1.

The other two equalities are obtained by simply interchanging p with q.

2.8.1. Cauchy Inequality#

Theorem 2.61 (Cauchy inequality)

2aba2+b2.

Proof. Note that:

(ab)20a22ab+b202aba2+b2.

2.8.2. Interpolation Inequality for ex.#

Theorem 2.62

If t[0,1] then:

eta+(1t)btea+(1t)eb.

Proof. This is a direct implication of the fact that ex is convex.

2.8.3. Young’s Inequality#

Theorem 2.63 (Young’s inequality)

Let p(1,). Let q be the conjugate exponent of p. Let a,b0, the following holds true:

abapp+bqq.

Note that for the special case of p=q=2, we obtain

aba22+b22

which is same as the Cauchy inequality. Thus, Young’s inequality is a generalization of Cauchy inequality.

Proof. For a=0 or b=0, the inequality is obvious. We shall now consider the case where a>0 and b>0.

Let λ=1p. Let t=apbq. Putting this in (2.3), we obtain:

(apbq)1p11p+1papbqabqp1papbq+1qabqpbq1pap+1qbqab1pap+1qbq.

We used the fact that:

qp+q=q(1p+1)=q1q=1.

Recall that (2.3) is an equality only if t=1 giving us:

apbq=1ap=bq.

Following is an alternative proof. This proof exploits the fact that ex is convex.

Proof. For a=0 or b=0, the inequality is obvious. We shall now consider the case where a>0 and b>0.

ab=exp(ln(ab))=exp(lna+lnb)=exp(1pplna+1qqlnb)=exp(1pln(ap)+1qln(bq))1pexp(ln(ap))+1qexp(ln(bq))=app+bqq.

In this derivation, we used the fact that ex is strictly convex.

2.8.4. Hölder’s Inequality#

Theorem 2.64 (Hölder’s inequality)

Let p,q be conjugate exponents with 1<p<. For any integer n1, assume that a1,,an and b1,,bn are non-negative.

Then

k=1nakbk(k=1nakp)1p(k=1nbkq)1q.

Proof. Let

A=(k=1nakp)1p and B=(k=1nbkq)1q.

If AB=0 (i.e., either A=0 or B=0 or both) then either all ai or all bi must be zero and the inequality is obvious.

Now, consider the case AB>0; i.e., A>0 and B>0.

Observe that:

k=1nakpAp=1=k=1nbkqBq.

Letting h a=akA and b=bkB and applying Young's inequality, we get:

akAbkBakppAp+bkqqBq.

Summing over 1kn, we obtain:

k=1nakAbkB1pk=1nakpAp+1qk=1nbkqBq=1p+1q=1.

Hence,

k=1nakbkAB(k=1nakp)1p(k=1nbkq)1q

as desired.

2.8.5. AM-GM Inequalities#

These inequalities establish relationship between arithmetic mean and geometric mean of a set of nonnegative real numbers.

We start with the simplest one.

Theorem 2.65 (AM-GM inequality for two numbers)

Let a,b0. Then

aba+b2.

Proof. We proceed as follows:

(ab)20a22ab+b202aba2+b24aba2+b2+2ab4ab(a+b)2ab(a+b2)2aba+b2.

Theorem 2.66 (Unweighted AM-GM inequality)

Let a1,a2,,an0. Then

(i=1nai)1n1n(i=1nai).

Proof. If any of the numbers is 0, then the geometric mean is 0 and the inequality is satisfied trivially. Thus, we shall assume that all numbers are positive.

We prove this by Cauchy induction.

  1. The base case for n=2 is proved in Theorem 2.65 above.

  2. We show that if the inequality is true for some n, then it is also true for 2n.

  3. We then show that if the inequality is true for some n, then it is true for n1 too.

  4. Then, by principle of Cauchy induction, the proof is complete.

(n)(2n)

Assume that the inequality holds true for any set of n positive numbers. Now for 2n numbers:

a1++a2n2n=a1++ann+an+1++a2nn2.

Since the inequality holds true for n, hence:

a1++anna1ann and an+1++a2nnan+1a2nn.

Thus,

a1++a2n2na1ann+an+1a2nn2.

The R.H.S. is an arithmetic mean of 2 numbers. Applying Theorem 2.65:

a1ann+an+1a2nn2a1annan+1a2nn=a1a2n2n.

Combining, we get the desired result:

a1++a2n2na1a2n2n.

(n)(n1)

By induction hypothesis, for any n positive numbers, we have:

a1++anna1ann.

Choose:

an=a1++an1n1.

Then

a1++ann=a1++a1++an1n1n=a1++an1n1.

Thus, we have:

a1++an1n1a1an1a1++an1n1n.

Taking n-th power on both sides, we get:

(a1++an1n1)na1an1a1++an1n1(a1++an1n1)n1a1an1a1++an1n1a1an1n1

as desired. The division by a1++an1n1 is valid since it is a positive number.

By Cauchy induction, the proof is complete.